(untitled) (Research, Society and Development, 2021)
Introduction: For the ideal performance of health professionals, their training must be carried out with quality. Therefore, the practice of internships becomes indispensable in universities, especially in areas that demand a lot of knowledge, such as the Intensity Therapy Unit (ICU). Thus, the objective of this study is to analyze the perception of Physiotherapy students about their supervised internships in an ICU. Methods: In this cross-sectional analytical and quantitative study, 29 students from the 10th semester of Physiotherapy answered closed and open questions in which situations and experiences during the internship in the Intensive Care Unit. Results and Discussion: Most students had not been in therapy units previously, besides finding the internship time inadequate. However, they feel able to work in this sector and believe that the internship was a great learning experience for improving clinical practice and humanizing the patient. Conclusion: Physiotherapy students still have difficulties, while doing internships, which can be remedied with greater engagement in the pedagogical coordination of their courses and their teachers. However, the opportunity to intern in Therapy Units is fundamental for the professional growth of these students.